Pengaruh Sustainability Reporting, Dewan Komisaris Independen Terhadap Financial Distress dengan Sales Growth Sebagai Variabel Moderasi - Zahranie, Aurora Maulida; Lukita, Carolyn; Nasihin, Ihsan (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2024)
The phenomenon that occurred in this research regarding the growth ratio in chemical sector manufacturing companies in Indonesia in 2019-2022 experienced a decline due to fluctuations which would result in financial difficulties. This research aims to determine the influence of sustainability reports, an independent board of commissioners on financial distress and sales growth as a moderating variable. The data collection technique is downloading annual reports from the official Indonesian Stock Exchange website www.idx.co.id or chemical sector manufacturing company websites, so that there are 25 companies as a population with a sample size of 100 using a purposive sampling method. Data processing with SmartPLS version 4 software uses a partial least squares (PLS) approach. The results of this research show that the variable sustainability report, independent board of commissioners has a significant influence on financial distress. Sales growth can moderate the influence of the sustainability report on financial distress and the influence of the independent board of commissioners on financial distress.